Microtest to accompany Moore['s] The basic practice of Statistics - Moore, David S.; Delta Software, Inc. (Omaha, Neb. : Delta Software, 1995)
A menu-driven test preparation system (Microtest, version 7.2) which operates on a testbank for the textbook: The basic practice of statistics (c1995). Allows user to produce test questions which can be either user or system-selected on a random basis from among some or all of the chapters of the textbook. Features include printing copies of the test, archiving a large number of tests, and the ability to create multiple versions of a test by scrambling the order of questions.
Title from disk label.
Test bank data based on: The basic practice of statistics / David S. Moore. c1995.
System requirements: IBM PC or compatible; 384K RAM; DOS 3.0 or higher; 80-column monitor; 80-column or more printer.
LC copy has 2 copies of guide.
Keywords: Statistics -- Examinations, questions, etc. -- Databases; Examinations -- Questions -- Software